Aromatic amines contents of cigarette butts: Fresh and aged cigarette butts vs unsmoked cigarette. (August 2022) - Dobaradaran, Sina; Mutke, Xenia A.M.; Schmidt, Torsten C.; Swiderski, Philipp; De-la-Torre, Gabriel E.; Jochmann, Maik A.
Abstract: Cigarette butts (CBs) are some of the most abundant waste items in the environment and may contain high levels of different toxic chemicals, such as aromatic amines (AAs). However, to this date, there is no comprehensive study on the role of CBs in the emission of AAs into the environment. The present study investigated for the first time the concentration levels of 10 primary aromatic amines (PAAs), including ANL, p-TOL, m-TOL, o-TOL, 2, 6-DMA, o-ASD, 2-NA, 1-NA, 3-ABP, and 4-ABP that were measured and compared in unsmoked cigarette, freshly smoked CBs, and CBs collected from urban streets (named here aged CBs). The mean levels of ∑PAAs in different sample categories were statistically significantly different and the mean level order was as freshly smoked CBs > aged CBs > unsmoked cigarette with the values of 3.43, 2.12 μg g −1, and 0.28 μg g −1, respectively. The levels of ∑PAAs, ANL, o-ASD, 2, 6-DMA, 2-NA, and ∑TOL dramatically increased by 12.26, 4.05, 8.46, 10.41, 4.78, and 28.84 times, respectively, right after smoking comparing the freshly smoked CBs samples and unsmoked cigarette. The results also showed a substantial decrease in the levels of PAAs (except o-ASD) in the aged CBs samples compared to freshly smoked CBs. The levels of ∑PAAs, o-ASD, 2, 6-DMA, ∑TOL, ANL, 2-NA, 1-NA, and ∑ABP decreased 1.62, 1.09, 1.91, 3.20, 3.42, 2.63, 2.00, and 1.88 times, respectively. Considering the average PAAS content and estimated CBs littered worldwide every year, freshly smoked CBs can theoretically emit 2.9 tons of ∑PAAs into the environment annually. Considering other chemicals that may also be released into the environment via CBs (beside PAAs), we can consider CBs as a critical source of toxic compounds into the environment and water bodies. Graphical abstract: Image 1 Highlights: 10 aromatic amine (AAs) levels of cigarette butts (CBs) determined for first time. AAs of fresh CBs increased after smoking compared to unsmoked cigarette. CBs can act as a AAs carrier in the environment and contaminate water bodies. Mean level order of AAs was as freshly smoked CBs > aged CBs > unsmoked cigarette. Between all measured AAs, o-ASD had the highest levels in CBs.